Cardiac Haemorrhage: An Extreme Presentation of Leptospirosis - Razuin R1,2, Nurquin F. S2 , Nur A. R. P.2 , Julina M. N.3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Leptospirosis is a worldwide disease with significant morbidity and mortality. The severe form of the disease may present with cardiac and pulmonary involvements resulting in multi-organ failure. Cardiac manifestations of leptospirosis include arrhythmia, cardiomegaly, petechial haemorrhages, pericarditis and myocarditis. Case report: We report a case of a 10-year-old boy who was having shortness of breath and collapsed at home. At the emergency department, he was having refractory hypotension with electrocardiogram (ECG) showing sinus tachycardia. The liver and cardiac enzymes were markedly raised. The full blood count showed leukocytosis. It was concluded that he was in septicaemic state with acute multi-organ failure of unknown cause. He succumbed to the illness approximately 8 hours after the hospital admission. At autopsy, the lungs, liver and spleen were markedly congested. Pericardial effusion was noted. The heart showed extensive areas of petechial and confluent haemorrhages involving almost the entire epicardial surface of the right and left ventricles. Massive subendocardial haemorrhage was also observed upon sectioning of the left ventricular chamber. Histopathology examination corroborated that haemorrhages were present in the heart, lungs and the liver. Laboratory investigations revealed positive Leptospira IgM antibody, confirmed by positive Leptospira PCR. The cause of death was concluded as cardiac and pulmonary haemorrhages secondary to leptospirosis. Conclusion: Cardiovascular involvement in leptospirosis may manifest as rapidly deteriorating illness with clinical evidence demonstrable from the ECG changes and raised cardiac enzymes. Recognizing these signs early may help to improve outcomes.